2012
DOI: 10.3109/13693786.2012.660203
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of dermatophytes by the antimicrobial peptides human β-defensin-2, ribonuclease 7 and psoriasin

Abstract: Previous studies have described some antibacterial effects of antimicrobial peptides (AMPs) expressed in human skin, but little is known about their possible activity against dermatophytes. Therefore we have tested the effects of human β-defensin 2 (hBD-2), ribonuclease 7 (RNase 7) and psoriasin on the in vitro growth of four dermatophyte species. Germinating conidia of Trichophyton rubrum, T. mentagrophytes, Microsporum canis and Epidermophyton floccosum were exposed in vitro to hBD-2, RNase 7, psoriasin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…One interpretation of these results is that IL-22 has a protective role during T. rubrum infection, such that the level of the antimicrobial hBD-2 is upregulated in patients who have low DEFB4 CN and in whom the hBD-2 level is insufficient for an immune response against T. rubrum, which increases their susceptibility to infection. This is supported by a study showing that hBD-2 inhibits T. rubrum growth in vitro (Fritz et al, 2012). Consequently, T. rubrum may induce IL-22 production either directly or indirectly by stimulating other factors known to enhance IL-22, such as tumor necrosis factora and IL-1b (Sonnenberg et al, 2010), leading to the upregulation of DEFB4 gene expression and increased production of hBD-2.…”
Section: Discussionmentioning
confidence: 91%
“…One interpretation of these results is that IL-22 has a protective role during T. rubrum infection, such that the level of the antimicrobial hBD-2 is upregulated in patients who have low DEFB4 CN and in whom the hBD-2 level is insufficient for an immune response against T. rubrum, which increases their susceptibility to infection. This is supported by a study showing that hBD-2 inhibits T. rubrum growth in vitro (Fritz et al, 2012). Consequently, T. rubrum may induce IL-22 production either directly or indirectly by stimulating other factors known to enhance IL-22, such as tumor necrosis factora and IL-1b (Sonnenberg et al, 2010), leading to the upregulation of DEFB4 gene expression and increased production of hBD-2.…”
Section: Discussionmentioning
confidence: 91%
“…The strains were identified by established morphologic and physiologic criteria [9]. Microconidia were prepared as recently described [6].…”
Section: Methodsmentioning
confidence: 99%
“…Although the role of AMP to control the growth of bacteria on the skin surface and to protect the skin from infection is widely recognized, the role of AMP in tinea is less explored. Recently, it has been reported that AMP are induced in the lesional epidermis of tinea patients [5] and that the skin-derived AMP psoriasin, hBD-2 and RNase 7 are able to inhibit the growth of dermatophytes in vitro [6]. Thus, there is increasing evidence that AMP may also play an important role in the innate cutaneous defense against dermatophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Humoral-mediated immunity is also involved in fungal infections and mediates the protection against many fungi (Candida spp., T. rubrum) [42], increasing epidermal proliferation and facilitating dermatophyte elimination; however, the exact role of this immunity is uncertain [43][44][45]. It is clear that some parts of the immune system contribute more than others, but they are all important for the overall protection [46].…”
Section: Fungal Pathogenesismentioning
confidence: 99%